Comparing the performance of players unknown Battle Ground (PUBG) mobile app on iPhone X and Samsung S9 Plus smartphones - Mkpojiogu, Emmanuel O.C.; Sherriff, Gomo; Hussain, Azham; Hashim, Wahidah (Science and Engineering Research Support Society, 2020)
In this paper, we present the results of a comparative evaluation of the performance of the Players Unknown Battleground (PUBG) Mobile app on iPhone X and Samsung S9 Plus smartphones. The outcome indicates that Samsung S9 Plus performed better than iPhone X as perceived by players of the PUBG mobile game. This finding suggests that the quality of iPhone X for PUBG mobile app play should be enhanced toimprove on the experience of its users